Licornus Roewer, 1932: newly transferred to Ampycinae and first record of the family Gonyleptidae (Opiliones: Laniatores) from Venezuela - M., Osvaldo Villarreal; Kury, Adriano B. (Zootaxa, 2012)
Licornus tama sp. nov. is described from Táchira State in Venezuelan Andes. This is the first record of real Gonyleptidaefrom this country, although in the past some Venezuelan species, currently placed in other families, have been assigned toGonyleptidae. The genus Licornus Roewer, 1932 had hitherto two species, both endemic to Ecuador. Male genitalmorphology of a species of Licornus is for the first time illustrated and described. Original placement of Licornus in theCranaidae: Cranainae is not supported by morphology of the included species and Licornus is here formally placed in Gonyleptidae: Ampycinae. An emended diagnosis is given to Ampycinae.